Potensi Limbah Perkebunan Kelapa Sawit Sebagai Sumber Energi Alternatif Terbarukan Di Wilayah Kalimantan Barat - Fauzi, Fauzi (Faculty of Engineering, Universitas Tanjungpura, 2017)
Abstractâ€“ The area of oil palm plantations spread in 12 (twelve) regencies and 1 (one) city in West Kalimantan until 2016 has reached more than 1.4 million hectares. In addition to producing the main products of CPO, the oil palm plantation industry also produces biomass waste which, if not treated properly, will have adverse impacts on the environment. Solid waste from the processing of fresh fruit bunches can be utilized as fuel boiler driving steam turbine power plant. Liquid waste can be processed into biogas for fuel gas engines or gas turbines. While solid waste from stems and palm oil plant bark can be processed to produce bioethanol. Solid waste from the palm oil processing plant that has not been optimally utilized in the form of empty bunches of volumes reached more than 1.077.087 tons/ year and shell 301.584 tons/ year. Of these two solid wastes have the potential to generate energy of 21.826 Â TJ/yr. While liquid waste has the potential to produce methane gas of 66.779 on/year with a calorific valu of 3.606 TJ /yr. The total energy produced by solid and liquid waste is 25.432 TJ/yr. If used as fuel boiler or gas engine with heat transfer value into energy (efficiency) of 21,5%, will be generated electrical energy equal to 1,466,159 MWh/yr or equivalent with power plant with capacity more than 167 MW that operate throughout the year. From the processing of stem and oil palm plant stem if in every year re-planting of 4% of the plant area (48,344 ha), will potentially produce bioethanol 698.861 kL/yr. From utilization of palm oil processing waste as raw material of energy replacing fossil fuel will have positive impact to environment and potency to reduce CO2 emission up to 3,047,808 t-CO2/yr. Utilization of waste oil palm plantations into energy will provide financial benefits and environmental improvement.Â Keywords- palm oil, biomass waste, energy, environment